LEARNING OUTCOMES IN ONLINE AND DISTANCE LEARNING: A STUDY OF LEARNERS’ EXPERIENCE - Soon Seng Thah,; Latifah Abdol Latif, (2016)

(untitled)
ODL institutions have often been seen as possessing an innovative and technology-driven delivery approach in teaching and learning practices. The key is in the online delivery of instruction for working learners. Online delivery would require e-tutoring and the use of learning materials to faciltate instruction across diverse groups of learners in a ubiquitous learning environment. This study focuses on Open University Malaysia’s approach in leveraging online learning for its stakeholders via its academic programmes. This study attempts to ascertain factors which affect the learning outcomes in ODL. The study was conducted via web survey on 397 learners enrolled at Open University Malaysia from 2012 to 2015. The sample consisted of learners aged between 18 to 64 years. The measurement of learning outcomes was determined via a 5-point Likert rating scale questionnaire. In addition, open-ended responses were also elicited to confirm quantitative findings. Three key constructs emerged from factor analysis, i.e. i. teaching and materials, ii. e-tutoring, and iii. learning experiences. These 3 factors were then confirmed using Structural Equation Modeling techniques to determine model fit derived from exploratory factor analysis. The results show a good fit of the hypothesised model with the structure of the data. As ODL institutions enrol learners from various demographic groups, this study attempted to look into whether demographic differences such as gender, age categories, experience in online learning, learners’ CGPA results and time spent on online learning had a significant bearing on learning outcomes. The findings show that female learners perceived teaching and materials, e-tutoring and learning experiences better than male learners but these differences are statistically not significant. From the perspectives of age groups, the study found that age maturity results in slight differences in teaching and outcomes, i.e. the older the learners the more positive the outcomes. However, across the different age groups, no statistical differences exist (p > .05). This study also found no significant differences (p > .05) in the perception of outcomes between learners who had previous experience in online learning compared to those who had not. Based on the learners’ CGPA scores, this study shows a general tendency for learners who score high in CGPA to also perceive positively in the 3 constructs, viz. teaching and materials, e-tutoring and learning experiences. However, no significant differences (p > ,05) existed across the different CGPA groups. An interesting finding of this study is that the time learners spent in logging-in to the online sessions - this had a significant effect on the outcomes (p < .05). The study concluded that the more time expended in logging-in online, the better would be the outcomes on teaching and use of the materials, e-tutoring and learning experiences. Based on the empirical evidence of the study, this paper puts forth a proposition that ODL is an effective delivery system for working learners - leading to good learning outcomes. ODL can guide learners towards the acquisition of desired knowledge and skills needed to excel in academic pursuits among working learners. Key Words: learning outcomes, online and distance learning, programme evaluation